Efeito de um complexo de rutênio em células de câncer de mama em diferentes modelos 2D e 3D in vitro e in vivo - Becceneri, Amanda Blanque (2019)
Cancer is among the leading causes of morbidity and mortality in the world. Specifically, breast cancer is an extremely heterogeneous disease, being composed of different subtypes and this heterogeneity makes treatment difficult, since each disease subtype has specific characteristics and requires differentiated treatment. Despite progress in the field of molecular and cellular biology, the development of new antitumor drugs is still a major challenge, as many drugs currently used are not selective for tumor cells, making the treatment difficult and causing unwanted and adverse effects on patients. Metal complexes are being used as an alternative for cancer treatment and several other diseases, and ruthenium complexes have been gaining prominence for cancer treatment due to their unique characteristics and important results. The aim of the present work was to select among different molecules a new ruthenium complex, which would be the candidate for an antitumor drug and to evaluate the effects of the selected complex through in vitro studies on breast cells in two-dimensional (2D) and three-dimensional cell culture (3D) and in vivo toxicity and genotoxicity studies. The results demonstrated that the complex Ru(ThySMet) was the most active against MDA-MB-231 breast tumor cells among the three complexes after 24 h incubation and in in vitro 2D tests induced cytotoxicity, inhibited invasion, adhesion, morphology and apoptosis-induced alteration, DNA damage and nuclear fragmentation of MDA-MB-231 tumor cells in lower concentrations compared to MCF-10A non-tumor cells, suggesting the selective action of this complex for tumor cells. In vitro 3D experiments with 24 h incubation with the complex Ru(ThySMet) also show higher cytotoxicity to T4-2 and MDA-MB-231 tumor cells compared to S1 and MCF-10A non-tumoral breast cells and induced apoptosis in different culture models and DNA damage. Also, the complex reverses the malignant phenotype of T4-2 breast cancer cells due to a suppression of substances related to this process, such as EGFR, p50 NFκB and β1 integrin. In vivo, the complex Ru(ThySMet) does not cause toxicity and caused DNA damage only at the highest dose administered. An analysis of the effect of the complex Ru(ThySMet) synthesized on a microemulsion nanostructured system on different breast cells, MDA-MB-231, MCF-10A and 4T1.13ch5T1 and on Balb/C 3T3 fibroblasts, exhibited that with 48 h of incubation there was an increase in selectivity of this new complex and also that this complex was able to alter the morphology and inhibit cell migration of tumor cells with more specificity than non-tumor cells, but its mechanism of action was altered causing cells to die from necrosis rather than apoptosis. Taken together, the results indicate that the complex Ru(ThySMet) has potential for breast cancer therapy and ¬¬further studies should be conducted to prove this potential.